DAMPAK KEBIJAKAN KEPESERTAAN MANDIRI JAMINAN KESEHATAN NASIONAL (JKN) DI YOGYAKARTA - Endartiwi, Sri Sularsih; Trisnantoro, Laksono; Hendrartini, Yulita (Jurnal Kesehatan Masyarakat, 2017)
ABSTRACT Background: The implementation of National Health Insurance (JKN) had been started since 1 January 2014. In the first semester, several problems are found in the admission department. First, it is found that there about 10% or 4,400 participants are they who are suffering for disease or have used the health insurance. Second, there are participants who are already undergoing treatment at the hospital and turning out a large cost then they are newly registered as JKN participants. Objective: To monitoring the implementation of independent participants policy of the National Health Insurance (JKN) in Yogyakarta. Methods: This research is a case study with qualitative and quantitative approaches. Research will be conducted in the BPJS Yogyakarta, Academic Hospital of the Gadjah Mada University, the Office of the Provincial Council Commission D Yogyakarta, Yogyakarta Provincial Health Office in April 2015. The study was conducted by in-depth interviews as well as filling the form of independent patient data. Results: The viewpoint of the national health insurance participant is positive. Independent participants consider it is important to enforce the national health insurance program. Participants also consider it is reasonable for them to pay the monthly dues. Their motivation to register as an independent participant is already going to take advantage of health services, a precaution and to protect themselves against the risk of illness. Compliance participants who pay dues are in arrears to pay dues by 27%. The impact of independent participants is people who are already sick or have health services and will utilize it for about 123% claims ratio. It is better for the hospital to do socialization, add more facilities and infrastructure, improve the hospital services, leadership and bureaucracy. Conclusion: Independent participants policy is to motivate people who are already sick to register as a participants and 27% of participants who had recovered in arrears to pay.The fundamental improvement in the independentparticipants policy is an improvement on Presidential Decree No. 12 of 2013, especially chapters 4 and 5, Presidential Decree No. 111 of 2013 chapter 16F, and The Health Minister regulations No. 71 of 2013 article 21 paragraph 1 and 22 paragraph 1 Keywords: impact, independent participant,National Health Insurance (JKN)